Improvement in Carbonation Resistance of Portland Cement Mortar Incorporating γ-Dicalcium Silicate. (5th August 2019) - Chen, Zhengxin; Lee, Yunsu; Cho, Hyeongkyu; Lee, Hanseung; Lim, Seungmin
Abstract : In this study, γ -dicalcium silicate ( γ -C2 S) was incorporated into ordinary Portland cement (OPC) to sequester CO2 to enhance the carbonation resistance of cement-based composite materials. γ -C2 S can react with CO2 rapidly to form vaterite and high dense SiO2 gel which could block the pores off and then inhibit further diffusion of CO2 into the system. Cement mortar specimens containing 0%, 5%, 10%, 20%, and 40% γ -C2 S as cement replacement were prepared. After water curing for 28 days followed by curing in an environmental chamber for 28 days, the specimens were then exposed to an accelerated carbonation with 5% CO2 concentration for 28 days. The carbonation depth of the cement mortar with a low replacement rate (5% and 10%) was lower than that of the OPC mortar at all ages due to the sequestration of CO2 by γ -C2 S. However, the cement mortar with a high replacement rate (20% and 40%) showed less carbonation resistance due to the dilution effect of γ -C2 S replacement and increase in initial porosity caused by nonhydraulic characteristic of γ -C2 S.